Patient-Specific Age: The Other Side of the Coin in Advanced Mesenchymal Stem Cell Therapy - Schimke, Magdalena M.; Marozin, Sabrina; Lepperdinger, Günter (Frontiers in Physiology, 2015)
Multipotential mesenchymal stromal cells (MSC) are present as a rare subpopulation within any type of stroma in the body of higher animals. Prominently, MSC have been recognized to reside in perivascular locations, supposedly maintaining blood vessel integrity. During tissue damage and injury, MSC/pericytes become activated, evade from their perivascular niche and are thus assumed to support wound healing and tissue regeneration. In vitro MSC exhibit demonstrated capabilities to differentiate into a wide variety of tissue cell types. Hence, many MSC-based therapeutic approaches have been performed to address bone, cartilage, or heart regeneration. Furthermore, prominent studies showed efficacy of ex vivo expanded MSC to countervail graft-vs.-host-disease. Therefore, additional fields of application are presently conceived, in which MSC-based therapies potentially unfold beneficial effects, such as amelioration of non-healing conditions after tendon or spinal cord injury, as well as neuropathies. Working along these lines, MSC-based scientific research has been forged ahead to prominently occupy the clinical stage. Aging is to a great deal stochastic by nature bringing forth changes in an individual fashion. Yet, is aging of stem cells or/and their corresponding niche considered a determining factor for outcome and success of clinical therapies?